Управління конкурентоспроможністю організації на ринку інтелектуальної праці - Грішнова, О.А.; Сокуренко, С.П. (Інститут демографії та соціальних досліджень НАН України, 2008)
В статье исследованы особенности интеллектуального труда и рынка интеллектуального труда, выявлены основные факторы конкурентоспособности организации на этом рынке, обоснованы основные направления управления предприятием с целью достижения такой конкурентоспособности. In the article author investigates special features of intellectual labour and intellectual labour market, defines the major factors of organization competitiveness on this market, and substantiates main directions of organization management in the framework of competitiveness achievement.